Novel biobased copolyesters based on 1, 2-propanediol or 2, 3-butanediol with the same ethylene skeletal structure as PETG. (17th January 2018) - Kim, Ji-Hyun; Kim, Jong-Ryang; Ahn, Cheol-Hee
Abstract: New potentially biobased copolyesters having the same ethylene skeletal structure as poly(ethylene glycol-co-1, 4-cyclohexanedimethanol terephthalate) (PETG) were synthesized based on 1, 2-propanediol (1, 2-PD) or 2, 3-butanediol (2, 3-BD) with 1, 4-cyclohexane dimethanol (CHDM). The compositions of each copolyester were confirmed using 1 H-NMR spectroscopy, and the detailed structure was analyzed using 2D NMR spectroscopy. In order to observe the effect of the lateral methyl groups on the microstructure and randomness in the sequences of the copolymers, 13 C-NMR spectroscopy analysis was performed. The thermal properties, mechanical properties, and crystallinity of the copolyesters were analyzed using differential scanning calorimetry, thermogravimetric analysis, universal testing machine, and wide-angle X-ray diffraction. Depending on the number of the lateral methyl groups and the contents of the ethylene diol units, the copolyesters displayed different densities, glass transition temperatures (Tg ), degrees of randomness and mechanical properties; however, a notable difference was not observed in thermal stability or crystallinity. Graphical abstract: Highlights: Synthesis of new copolyesters based on 1, 2-PD or 2, 3-BD compared to EG. Lower molecular weight obtained for copolyesters increasing secondary hydroxyl group. Microstructure analysis using 13 C NMR for sequence and degree of randomness. The lateral methyl group increased Tg, Young's modulus, and yield strength.